1986
DOI: 10.1017/s0022029900024821
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the fat composition and concentration of citrate and related metabolites in cows' milk

Abstract: SUMMARYSeasonal variations were observed in the proportion of long-chain (C18 and over) and medium-chain (C6–14) fatty acids (FA) in milk fat. Long-chain FA were proportionately higher during the period June to October. Changes were also observed in the concentrations of citrate, isocitrate and 2-oxoglutarate in milk. Changes in [isocitrate]: [2-oxoglutarate] correlated positively with changes in the proportion of long-chain FA in milk fat and negatively with the proportion of medium-chain FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Trans -C18:1 fatty acids and CLA in milk fat increased between days 8 and 29, and this may be interpreted as an indication of increased herbage intake. The increase in LCFA concentration in milk fat between days 8 and 29 in this study corresponds with earlier ndings on changes in milk fat composition when cows are on pasture (Faulkner et al, 1986;Coulon et al, 1988;Hinrichs et al, 1992).…”
Section: Plasma Glucose Insulin and Nefasupporting
confidence: 92%
“…Trans -C18:1 fatty acids and CLA in milk fat increased between days 8 and 29, and this may be interpreted as an indication of increased herbage intake. The increase in LCFA concentration in milk fat between days 8 and 29 in this study corresponds with earlier ndings on changes in milk fat composition when cows are on pasture (Faulkner et al, 1986;Coulon et al, 1988;Hinrichs et al, 1992).…”
Section: Plasma Glucose Insulin and Nefasupporting
confidence: 92%
“…The concentration of citrate in milk is fairly high and citrate is known to form complexes with copper, thereby making it less powerful as a pro-oxidant. Faulkner et al (1986) reported a variation in concentration of citrate in milk during lactation. Citrate has also been reported to vary with feeding (Ormrod and Thomas 1979 ;Faulkner and Clapperton 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor is geographical, which determines the plant variety underlying the feeding of ruminants. The effects of seasonal and geographical factors on FA composition of the bovine milk fat were reported by many authors (Faulkner et al 1986;Lock & Garnsworthy, 2003;Alonso et al 2004; Thorsdottir et al 2004;Frelich et al 2009;Rutkowska & Adamska, 2011).…”
mentioning
confidence: 88%